Design and Implementation of Virtual Simulation Software to Display Information on Weather Indicators to Manage and Control Urban Policy-Making - Farsi, Mohsen; Matani, Mehrdad; Fallah, Ali; Bagherzadeh, Mohammadreza; Gholipourkenani, Yousef (AI and Tech in Behavioral and Social Sciences, 2024)
This research focuses on the design, implementation, and development of software using virtual simulation technology for data visualization, aiming to present urban statistical information through an innovative tool that transforms raw data into 3D models for observation and analysis. The tool consists of two main components: a web-based data entry panel for user-friendly data input or upload, and a 3D data visualization module where information is displayed in a virtual reality simulator. Adhering to the principles of originality, honesty, and integrity, the software enables researchers to convert raw data into 3D models, facilitating easier observation and extensive analysis of events. Consequently, researchers can record and view their data in 3D, analyze their observations to derive information and results, and enhance public understanding through the visualized display of their findings.